2012
DOI: 10.1007/s00128-012-0590-2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Polychlorinated Biphenyls (PCBs) and Evaluation of Hematological and Immunological Effects of PCB Exposure on Turtles

Abstract: Concentrations of total polychlorinated biphenyls (PCBs), Aroclor 1260, and 26 congeners were measured in liver, fat, and eggs of red-eared slider turtles (Trachemys scripta elegans) collected from ponds near or on the Paducah Gaseous Diffusion Plant (PGDP), Kentucky, USA. Concentrations of total PCBs (wet mass) ranged from 0.002 to 0.480 mg/kg, 0.028 to 0.839 mg/kg, and 0.001 to 0.011 mg/kg in liver, fat, and eggs, respectively. Concentrations of Arochlor 1260 did not exceed 0.430, 0.419, and 0.007 mg/kg in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…Moreover, exposure to glyphosate (Roundup V R ) induced a decrease in the total leukocyte counts in newborn broad snouted caiman (Caiman latirostris) (Siroski et al 2016). In a similar study in red-eared slider turtles, total white blood cell (WBC) counts were negatively correlated with concentrations of total PCBs and Arochlor 1260 (Yu et al 2012). Conversely, a study on loggerhead sea turtles reported that estimated WBC was positively correlated with levels of total PCBs and total TCDD-like PCBs, respectively (Keller et al 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, exposure to glyphosate (Roundup V R ) induced a decrease in the total leukocyte counts in newborn broad snouted caiman (Caiman latirostris) (Siroski et al 2016). In a similar study in red-eared slider turtles, total white blood cell (WBC) counts were negatively correlated with concentrations of total PCBs and Arochlor 1260 (Yu et al 2012). Conversely, a study on loggerhead sea turtles reported that estimated WBC was positively correlated with levels of total PCBs and total TCDD-like PCBs, respectively (Keller et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, in the same species, lysozyme activity was significantly but negatively correlated with whole blood concentrations of organochlorine (OC). Although the mechanism of altered lysozyme activity is not understood, the data suggested heterophil function might be affected in different ways after exposure to contaminants (Yu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, exposure to glyphosate (Roundup 庐 ) -an OP herbicide, induced a decrease in total leukocyte counts in newborn broad snouted caiman (Caiman latirostris) (Siroski et al, 2016). In a similar study in red eared slider turtles, total white blood cell (WBC) counts were negatively correlated with concentrations of total polychlorinated biphenyls (PCBs) and Arochlor 1260 (Yu et al, 2012). Conversely, a study on loggerhead sea turtles reported that estimated WBC correlated positively with levels of total PCBs and total TCDDlike PCBs (2, 3, 7, 8-tetrachlorodibenzop-dioxin), respectively (Keller et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, in the same species, lysozyme activity was significantly but negatively correlated with whole blood concentrations of organochlorine (OC). Although the mechanism of altered lysozyme activity is not understood, the data suggest that heterophil function might be affected in different ways after exposure to contaminants (Yu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dose-response studies provide an avenue of inquiry and indicate that PCBs can cause adverse impacts to individual turtles (e.g. Eisenreich et al 2009, Holliday et al 2009, Holliday & Holliday 2012, Yu et al 2012. Such studies can be advantageous for isolating the effect of exposure level to a particular contaminant on the performance of specific traits of individuals; however, implications of such studies of population-level endpoints remain unclear.…”
Section: Introductionmentioning
confidence: 99%